A comparative study of Cycloprovera and Depoprovera contraceptive methods. The menstrual patterns and continuation rates - Soetrisno, Soetrisno (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1993)
The change of menstrual patterns caused by progestogen only contraception may influence the womens psychologic condition and sometimes requires discontinuation of its usage. Cycloprovera, a monthly injectable contraceptive method, containing progestogen + estradiol cypionate is considered to overcome the problems. The study was aimed at comparing the menstrual pattern changes and continuation rates between Cycloprovera and Depoprovera acceptors.The study is a part of a multicentered study comparing menstrual pattern changes between Cycloprovera and HRP 102 acceptors conducted in 5 countries including 7 research centers in Indonesia. For each Cycloprovera acceptors recruited in Yogyakarta, one Depoprovera acceptor was selected as control. Menstrual patterns and continuation rates of both groups were followed up in 3, 6. 9 and 12 months after having first injection. From July 1, to December 31, 1990. 31 acceptor for each group were recruited from several family planning clinics in Yogyakarta. The comparability of the two groups was not statistically significant except for blood pressure level. However, it was not clinically significant. The normal menstrual patterns was significantly higher in Cycloprovera group compared to Depoprovera group (p<0.05). No amenorrhoea and drop-out among Cycloprovera acceptors, while among Depoprovera group were 19.4%, 35.5%, 38.7% and 9.7%, 19.3%, 29.0% after 3, 6 and 9 to 12 months respectively. The changes of menstrual patterns after 3 and 6 months were significantly higher among Depoprovera groups compared to Cycloprovera (p<0.05), however, after 9 to 12 months were not statistically different (p<0.05).It is concluded that the menstrual patterns and continuation rates of Cycloprovera acceptors are better compared to Depoprovera acceptors, and no drop-out among Cycloprovera acceptors.Key Words: Cycloprovera - Depoprovera - menstrual patterns - user continuation rate - family planning clinic